2014
DOI: 10.1111/acel.12241
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction reveals a metabolomic and lipidomic signature in liver of male mice

Abstract: Lipid composition, particularly membrane unsaturation, has been proposed as being a lifespan determinant, but it is currently unknown whether caloric restriction (CR), an accepted life-extending intervention, affects cellular lipid profiles. In this study, we employ a liquid chromatography quadrupole time-of-flight-based methodology to demonstrate that CR in the liver of male C57BL/6 mice: (i) induces marked changes in the cellular lipidome, (ii) specifically reduces levels of a phospholipid peroxidation produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 49 publications
(86 reference statements)
1
61
1
1
Order By: Relevance
“…Previous metabolomic analyses on the livers of C57BL/6 CR mice suggest that glycolysis, fatty acid oxidation and amino acid pathways are significantly altered (Collino et al ., 2013; Fok et al ., 2014; Jové et al ., 2014). These changes were consistent with studies that indicate metabolic reprogramming through the shift from lipogenesis to lipolysis during CR is beneficial in both male and female C57BL/6 mice (Bruss et al ., 2010; Kuhla et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous metabolomic analyses on the livers of C57BL/6 CR mice suggest that glycolysis, fatty acid oxidation and amino acid pathways are significantly altered (Collino et al ., 2013; Fok et al ., 2014; Jové et al ., 2014). These changes were consistent with studies that indicate metabolic reprogramming through the shift from lipogenesis to lipolysis during CR is beneficial in both male and female C57BL/6 mice (Bruss et al ., 2010; Kuhla et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2014). Furthermore, a recent lipidomic approach has demonstrated that CR significantly altered the hepatic lipidome in male C57BL/6 mice and caused a change in the relative abundance of specific triglycerides and phosphatidylethanolamines and reduced hepatic 1-palmitoyl-2-glutaryl-sn-glycero-3-phosphatidylcholine content, a specific product of phospholipid peroxidation (Jové et al 2014). Less susceptibility of membranes to peroxidation was explained on the basis of a redistribution in the type of unsaturation: CR increased monounsaturated fatty acids (MUFA) in liver, whereas the levels of PUFA were decreased without any observed changes in saturated fatty acids (SFA).…”
Section: Mitochondrial Fatty Acids Calorie Restriction and Longevitymentioning
confidence: 99%
“…Less susceptibility of membranes to peroxidation was explained on the basis of a redistribution in the type of unsaturation: CR increased monounsaturated fatty acids (MUFA) in liver, whereas the levels of PUFA were decreased without any observed changes in saturated fatty acids (SFA). These specific changes may be the result of a metabolic reprogramming leading to lower levels of oxidative damage which could contribute to the increased lifespan of CR mice (Jové et al 2014). …”
Section: Mitochondrial Fatty Acids Calorie Restriction and Longevitymentioning
confidence: 99%
“…According to these results, we hypothesized that the extended longevity found in the CRL‐fed group correlates with the higher MUFA content in mitochondria from these animals as detected in hepatocytes and skeletal muscle (López‐Domínguez et al ., 2013, 2015b). Furthermore, the decreased susceptibility of membranes to phospholipid peroxidation may improve mitochondrial function, a phenomenon likely linked to lifespan extension (Jové et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%